Factors Affecting Time to Engraftment During Autologous Stem Cell Transplantation in Patients With Multiple Myeloma*. (September 2021) - Bolaman, Ali Z.; Turgutkaya, Atakan; Yavaşoğlu, İrfan
Background: High-dose chemotherapy with autologous stem cell rescue (HDC-ASCR) is the most effective treatment in transplant-eligible patients with multiple myeloma (MM). The complication rate of the procedure in MM is low, but its complications can be high if engraftment is delayed. In this study, we aimed to evaluate engraftment determinants in patients with MM who undergo HDC-ASCR with cryopreserved products. Methods: We retrospectively reviewed MM patients who undergo HDC-ASCR from February 2015 to May 2018 at the Hematology Department of Adnan Menderes University Hospital. The induction and conditioning regimens were similar in all patients. The relationship between time to engraftment (TTE) and age, sex, infused stem cell (CD34) count, the number of transfused erythrocyte and thrombocyte units, MM type, stage, pretransplant bone marrow plasma cell ratio, pretransplant hemoglobin level, leukocyte and thrombocyte count, comorbidities such as diabetes mellitus, hypertension, and chronic kidney disease, and habits like smoking and alcoholism was investigated. Results: A total of 40 patients were evaluated. The mean stem cell count was 6.23 (±3.72) × 10 6 /kg. Spearman's analysis was used between TTE and the parameters for correlation. There were correlations found between TTE-stem cell count (CD34) and TTE-smoking. However, we did not find any correlation with the other aforementioned parameters. Conclusion: Our retrospective study supported that infused stem cell count was the main engraftment determinant during the procedure of HDC-ASCR with cryopreserved products in MM.